Business development strategy using canvas business model and SWOT analysis on Bedroomstore.id - Rizki, Septiani; Wijaya, Fanji (Institute of Computer Science (IOCS), 2024)
This research aims to provide business development recommendations based on SWOT analysis using a business development strategy based on the canvas business model. This strategy uses qualitative research with a descriptive approach. The information collected in this research comes from interviews with business owners and references from logistics diaries, electronic books and various sources whose accuracy has been confirmed by involving information collection strategies as study archives. Based on the research results, the canvas business model analysis produces several suggestions and recommendations which are analyzed using SWOT analysis so that the owner can develop his business. The recommended canvas business model proposal is one where the items are included in the Value Proposition elements by creating a design that is competitive or new. In the Customer Relations element, an item is included in the Channel element by marketing the product through participation in all online stores, and events.